Oral manifestation in leprosy: A cross-sectional study of 100 cases with literature review - Puneeta Vohra; Md Siraj UR Rahman; B Subhada; Rahul Vinay Chandra Tiwari; M S Nabeel Althaf; Monika Gahlawat (Journal of Family Medicine and Primary Care, 2019)
Background: Leprosy is a chronic granulomatous disease of the peripheral nerve and muscle of upper respiratory tract. Consequence to the neighboring primary site, oral lesions have been seen in 20--60% of patient with leprosy mainly lepromatous leprosy. The lepromatous nodules may be infective and may lead to the spread of disease and hence require proper diagnosis. Aim: To assess oral lesion in leprosy patients. To assess the disease and the occurrence of oral lesion according to age and gender. To detect any primary lesion in oral cavity and compare these lesions in duration to study. Materials and Methods: A total of 100 patients with leprosy were examined and there oral manifestations were recorded. Results: It was found that 70 (70%) leprosy patients showed oral manifestations. And 18 (25%) had chronic generalized periodontitis, 9 (12.8%) cases of oral melanosis, 7 (10%) atrophy of papillae and loss of taste sensation each, 6 (8.5%) complained of aphthous and candidiasis each, 5 (7.14%) depigmentation, and 4 (5.71%) smokers palate, oral submucous fibrosis, and fissured tongue. Conclusion: Our clinical findings are in conjugation with previous studies; however, as per the review of literature this is the first study worldwide where we have examined 100 cases of leprosy which has not been documented till date. We suggest that the lesser incidence of oral lesions observed recently compared to older reports because of more effective present treatment which is initiated earlier.